Targeting CD10 on B-Cell Leukemia Using the Universal CAR T-Cell Platform (UniCAR) - Mitwasi, Nicola; Arndt, Claudia; Loureiro, Liliana R; Kegler, Alexandra; Fasslrinner, Frederick; Berndt, Nicole; Bergmann, Ralf; Hořejší, Vaclav; Rössig, Claudia; Bachmann, Michael; Feldmann, Anja (International journal of molecular sciences, 2022)
Chimeric antigen receptor (CAR)-expressing T-cells are without a doubt a breakthrough therapy for hematological malignancies. Despite their success, clinical experience has revealed several challenges, which include relapse after targeting single antigens such as CD19 in the case of B-cell acute lymphoblastic leukemia (B-ALL), and the occurrence of side effects that could be severe in some cases. Therefore, it became clear that improved safety approaches, and targeting multiple antigens, should be considered to further improve CAR T-cell therapy for B-ALL. In this paper, we address both issues by investigating the use of CD10 as a therapeutic target for B-ALL with our switchable UniCAR system. The UniCAR platform is a modular platform that depends on the presence of two elements to function. These include UniCAR T-cells and the target modules (TMs), which cross-link the T-cells to their respective targets on tumor cells. The TMs function as keys that control the switchability of UniCAR T-cells. Here, we demonstrate that UniCAR T-cells, armed with anti-CD10 TM, can efficiently kill B-ALL cell lines, as well as patient-derived B-ALL blasts, thereby highlighting the exciting possibility for using CD10 as an emerging therapeutic target for B-cell malignancies.
Keywords: receptory antigenů T-buněk; T-Lymphocytes; immunotherapy; Antigens, CD19; Receptors, Antigen, T-Cell; T-lymfocyty; CAR T-cells; Neprilysin; chronická lymfatická leukemie; Humans; imunoterapie adoptivní; Leukemia, B-Cell; Leukemia, Lymphocytic, Chronic, B-Cell; leukemie B-buněčná; antigeny CD19; CD10; Immunotherapy, Adoptive; neprilysin; lidé